2016
DOI: 10.1097/ijg.0000000000000254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Biomechanical Properties in Patients With Thyroid Eye Disease Using Ocular Response Analyzer

Abstract: In TED patients, CH seems to be lower than in normal subjects. GAT might underestimate the IOP due to differences in corneal properties of cornea in TED patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…Moghimi et al evaluated TED patients and reported the same findings as in the previous study. 14 These findings and our study results suggest that there is a strong relation between the autoimmune thyroid diseases -HT and GD. The etiology of HT and GD involves common pathways in which thyroid-reactive T cells escape tolerance and infiltrate the thyroid, and unique pathways in which these thyroid-reactive T cells either cause thyroid cell death (in HT) or stimulation (in GD).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moghimi et al evaluated TED patients and reported the same findings as in the previous study. 14 These findings and our study results suggest that there is a strong relation between the autoimmune thyroid diseases -HT and GD. The etiology of HT and GD involves common pathways in which thyroid-reactive T cells escape tolerance and infiltrate the thyroid, and unique pathways in which these thyroid-reactive T cells either cause thyroid cell death (in HT) or stimulation (in GD).…”
Section: Discussionsupporting
confidence: 76%
“…[10][11][12] Because of the fact that one of the most important manifestations of TED is corneal and ocular surface involvement, investigators have studied alterations in corneal biomechanical properties in TED patients. 13,14 There are also some studies about corneal microstructural changes using corneal pachymetry and confocal biomicroscopy in GD. 15,16 To the best of our knowledge, alterations in corneal biomechanical properties in patients with HT have not been studied in detail before.…”
Section: Introductionmentioning
confidence: 99%
“…This results were similar to those of ORA-based studies in which the CH level was lower in patients with TED than the control subjects. [ 17 18 19 ] The CH level was lower in ectatic corneal disorders,[ 20 21 ] and the lower CH level was realized as an independent risk factor for the glaucoma progression. [ 22 ] The inflammatory process in TED reduced the corneal damping ability[ 19 ] and could cause changes to the CH and HCDA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of the thyroid gland status on corneal biomechanical properties were not considered in previous reports in TED. [ 17 18 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the HKC, patients with keratoconus were included. The HKC includes also patients without obvious corneal abnormalities but with dysfunction of the thyroid gland, as thyroid disorders are suspected of leading to corneal biomechanical changes [ 7 ]. The diagnostic methods and goals of the HKC have been previously described in detail [ 8 10 ].…”
Section: Methodsmentioning
confidence: 99%